Covalent Immobilization of Peroxidase onto Hybrid Membranes for the Construction of Optical Biosensor - Lyubov Yotova; Ahmed Hassaan; Spaska Yaneva (International Journal Bioautomation, 2015)
The aim of this study is to covalently immobilize horse radish peroxidase (HRP) onto new hybrid membranes synthesized by the sol-gel method based on silica precursors, dendrimers and cellulose derivatives. This new system will be used for designing biosensor. For investigation of the properties of membranes, HRP was used as a modeling enzyme. Kinetic parameters, pH and temperature optimum were determined, and the structure of the membranes surface was examined. Results showed higher relative and residual activity of HRP immobilized onto membranes with cellulose acetate butyrate with high molecular weight CAB/H. This novel biosensor could offer a simple, cheap and rapid tool with enhanced sensing performance as well as having potentials to find application in medicine, pharmacy, food and process control and environmental monitoring.